(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
It was found that some problems occur in the Human Resource Department, and Billing and Collection Section of XYZ Company such as having difficulties in daily tasks and having an old-fashioned office equipment. This research aims to find solutions on problems that occur between the two departments, and to make work flow more efficient. Interviews were conducted with the representative of each department to identify the main problem. Surveys forms were designed to determine the main problem and if the proposed solutions can help the operations. The employees of Human Resources Department who participated in the survey perceived substantial problems due to lack of manpower and specific job descriptions for the HR staff due to the vacancy of payroll officer because of which, difficulties in finishing tasks on time were observed. In the Billing and Collection Section in Financial Accounting Division, the employees who participated in the survey experienced some problems regarding file back up and printing of invoice caused by technical issues in backing up of files and the department’s old school method of printing invoice which delays the distribution of invoice in other departments. The results demonstrate the need for additional payroll officer in order to organize the job of every staff, proper orientation of new employees regarding the company history, and proper job description for every staff. The results in billing and collection section show the need for using P.O.S machine in printing invoice.